The Effect of Micromechanical Surface Preparation and Adhesive Surface Modification Strategies on Resin-Matrix Ceramic Repair Bond Strength Using Universal Adhesive Containing Silane Agent - Klaisiri, Awiruth; Maneenacarith, Apichai; Sriamporn, Tool (European Journal of General Dentistry, 2024)
Objectives This research assesses the effect of the different micromechanical surface preparations and chemically adhesive surface modification strategies applied to resin-matrix ceramics (Shofu Block HC) repaired using resin composites.Materials and Methods Eighty resin-matrix ceramics were conducted and designed into eight groups of 10 specimens and surface treated with (1) micromechanical preparation with sandblast (SB) or hydrofluoric acid (HF), and (2) chemically adhesive techniques with HC primer (HC) and/or silane (Si) and/or conventional adhesive (AD) or universal adhesive (UA) designing are as follows: group 1, SB + HC; group 2, SB + HC + AD; group 3, SB + HC + Si + AD; group 4, SB + HC + UA; group 5, HF + HC; group 6, HF + HC + AD; group 7, HF + HC + Si + AD; and group 8, HF + HC + UA. An ultradent model was put on the specimen center, then filled resin composite. Mechanical testing instrument was used to determine the samples' microshear bond strength (MSBS). To inspect failure modes, a stereomicroscope was used for observing the debonded surfaces.Statistical Analysis To assess the data, a one-way analysis of variance was employed, and the significant level (p < 0.05) was established with Tukey's test.Results Group 3 (29.29 ± 2.58 MPa) and group 4 (28.34 ± 1.26 MPa) demonstrated the two maximum MSBS values. The minimum MSBS (10.02 ± 3.31 MPa) was discovered by group 5. Nevertheless, group 2's MSBS values (22.78 ± 2.44 MPa) differed significantly from the values for groups 3 and 4. All the fractured samples in groups 1, 5, 6, 7, and 8 had an adhesive failure pattern. Furthermore, group 3 presented the greatest mixed failures (40%).Conclusion The SB is the most effective protocol for producing micromechanical retention. The application of HC primer and Si agent prior to the adhesive agent is the best chemical adhesive strategy for sandblasted resin-matrix ceramic surfaces. Additionally, the application of HC primer before the use of UA containing acid-resistant Si is the best alternative chemical adhesive strategy for improving the MSBS.
Keywords: adhesive agent; hybrid ceramic; repair bond strength; surface treatment